Extent Of Compliance To Standard Precautions Among Healthcare Workers In Accredited Birthing Facilities In San Jose, Occidental Mindoro, Philippines - Asuncion, Cheryl; Pastrana, Nimfa; Salvador, Marciel (International Journal of Educational Research & Social Sciences, 2022)
This study was conducted to determine the extent of compliance of health care professionals employed in birthing facilities in the municipality of San Jose, Occidental Mindoro. Specifically, it sought to determine the demographic data of the respondents as to age, educational attainment and years of experience; investigate their level of compliance to standard precautions and examine if there exists a significant relationship between the demographic variables of the respondents and their level of compliance to standard precautions. There were 23 health workers who participated in the study. The main instrument used in the study is the CSPS, a standardized checklist for measuring compliance to SP. Results showed that health workers in birthing facilities in the municipality are young, graduates of bachelor’s degree and are new in the service. They are also highly compliant with SP. It was also found that age and experience are significantly related with compliance to SP. The researchers recommend that this study be replicated using other health professionals as respondents such as doctors since they are the ones who are most exposed to health hazards. It is also suggested that further studies be conducted considering other variables which are not covered in this study.